Environmental, Social, and Governance (ESG) Disclosure and Company Performance: Empirical Evidence in Indonesian Banking - Cahyaningtyas, Susi Retna; Muhsyaf, Saipul Arni; Husnaini, Wahidatul (Universitas Jember, 2024)
This study aims to analyze the relationship between ESG disclosure and company performance with a sample of banking companies listed on the Indonesia Stock Exchange in 2010-2021. Company performance is measured using Return on Assets (ROA), Return on Equity (ROE), Tobin's Q, and Stock Return (Ri). Furthermore, ESG disclosure is measured using the Global Reporting Initiative (GRI) standard for environmental and social disclosure, while governance disclosure is assessed using the GCG score based on POJK Number 55/POJK.03/2016 concerning the implementation of Governance for Commercial Banks, and Indonesian Regulation (PBI) Number 11/33/PBI/2009 concerning the Implementation of Good Corporate Governance for Sharia Commercial Banks and Sharia Business Units. This study uses a quantitative approach with the help of the Eviews 13.0 analysis tool. The results of this study indicate that environmental, social, and governance disclosures have no effect on ROA. While governance disclosures have a negative effect on ROE, in addition to environmental and social disclosures that have no effect on ROE. On the other hand, social and governance disclosures have a positive effect on Tobin’s Q, which is the opposite of environmental disclosures that have a negative effect. Meanwhile, environmental disclosures have a negative effect on stock returns, in addition to social and governance disclosures that have no effect on stock returns. Keywords: Disclosure; Environment; Social; Governance; Performance